Experimental investigation and system design of dishwasher heat pump system with R600a - Şeren, Erdoğan Mert. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2023., 2023)
In this thesis study, the effect of R600a/R290 zeotropic mixture on system performance was investigated in detail on a heat pump system adapted to the dishwasher and using pure R600a as the refrigerant. In this context, five different compositions of the mixtures were investigated experimentally, with the R290 composition in the refrigerant mixture ranging from 10% to 50% by mass. In experimental studies, energy consumption, power consumption, cycle time, heating capacity, and heating efficiency were mainly compared with the base system using pure R600a. Fundamentally, a gradual decrease in the dishwasher cycle time was noted, with the percentage of R290 increasing and the cycle time in the experiment using 50% R290 in the mixture decreased by 54 minutes (28.4%) compared to the base experiment with a cycle time of 190 minutes. Although increasing R290 ratios in the mixture offered a higher power consumption value, it increased the heating capacity, so increased power consumption did not always bring high energy consumption with it. In the experiment where a 60% R600a and 40% R290 mixture was applied, a cycle time of 160 minutes was obtained, and it was observed that the increase in heating capacity provided optimum heating efficiency by surpassing power consumption. In parallel, the energy consumption decreased by 10 Wh compared to the base experiment with an energy consumption value of 470 Wh. Also, this study created a sub-model for each component of the heat pump dishwasher, and then all models were combined to form a heat pump dishwasher cycle model. The dynamic behavior of the dishwasher has been validated for both pure R600a and the R600a/R290 mixtures. While the maximum deviation in the cabinet temperature of the dishwasher was 1.5 °C, the cycle time variance was 2 minutes throughout the cycle. In addition, although the maximum deviation in power consumption was 5.2%, a maximum deviation of 2.9% was observed in the energy consumption value. Thus, the outputs of the model and the experiment were relatively comparable.
Keywords: Dishwashing machines.; Heat pumps.